Correlation among immune response, morphogenesis of the granulomatous reaction and spleen lymphoid structure in murine experimental paracoccidioidomycosis - Soares, AMVC; Peracoli, MTS; Dos Santos, R. R. (B I O S Scientific Publishers Ltd, 2000)
We studied the correlation among cellular immune response, the pattern of lung granulomatous lesions and alterations in spleen lymphoid structure in Swiss mice inoculated intravenously with Paracoccidioides brasiliensis strain 18. The animals were evaluated at 24, 48 and 96 h after infection and further studied weekly for 18 weeks by: (i) the macrophage migration inhibition test with phytohemagglutinin (PHA) and P. brasiliensis antigen (PbAg); and (ii) histopathology of the lung and spleen lesions. One group of animals was gamma -irradiated (8 Gy), infected under the same conditions and evaluated for the pattern of lung granulomatous lesions and spleen lymphoid structure at 24, 48 and 96 h after infection. During the first week of infection, the non-irradiated animals presented a positive response to PHA and PbAg, compact granulomas in the lungs and a typical hyperplasia of the spleen white pulp. However, from weeks 2 to 5, a depression of the cell-mediated immunity (CMI) response to PHA and PbAg was observed in association with granulomas presenting only large mononuclear cells and lacking both giant cells and a peripheral halo of small mononuclear cells. This pattern of granuloma formation was similar to that seen in gamma -irradiated animals, whose cells involved in CMI were absent. After week 7, the non-irradiated animals showed granulomas characterized by the presence of giant cells and a peripheral halo of small mononuclear cells. This type of granuloma was formed concomitantly with recovery of the CMI and of the lymphoid structure of the spleen. The results showed a correlation among granulomas composed of large mononuclear cells, hypoplasia of the splenic tissue and impaired CMI. This correlation indicated that although granuloma morphogenesis per se does not depend on the activation of CMI, this response is important at later stages during modulation of the cellular composition of the granulomas.
Keywords: granuloma; immune response; lymphoid tissue; paracoccidioidomycosis